Cartografia geofísica do arcabouço estrutural da bacia potiguar emersa, com base em dados gravimétricos e magnéticos - Souza, Suelen Ferreira de (2015)
The study of sedimentary basins involves an integration of information acquired from the application of different methodologies. The Potential Methods, gravity and magnetic represent an effective methodology to study the tectonic framework of sedimentary basins, at a relatively cheap cost than another techniques. The present work presents the integration of different advanced techniques of geophysical processing in potential data (Reducing to Pole, Matched Filter, Horizontal Gradient and Tilt Derivative) which greatly assisted in characterization of geophysical expression of the main structural components of Potiguar Rift and it tectonic framework. The results allowed clearly identify the failed edges of the Potiguar Rift (Carnaubais, Apodi e Mulungu faults), as well as its internal components, Macau and Quixaba horsts, and the Apodi, Umbuzeiro and Boa Vista grabens. The expressive shear zones of it basement (Senador Pompeu, Jaguaribe, Portalegre, Açu, Florânia-Ângicos e Picuí João-Câmara) they also were evidenced by geophysical mapping as extensive sigmoidal alignments of NE-SW direction. The integration of geophysical data with geological data allowed the identification of eight tectonic geophysicist domains, with purpose of establishing the behavior of main crustal blocks of the Borborema Province bellow of the sedimentary package. The results provided by techniques also allowed the association of the above mentioned structures with the main stages of rifting by which passed the basin during its complex evolution. The trend NE-SW, that occurs as the main directional pattern in the adjacent regions to the Potiguar Rift, and also inside evidence a strong control of precambrian structures in basin formation, as well as the NW-SE deformation in the Rio Ceará-Mirim dykes swarms, the truncation of NE structures with Apodi Fault, and also the separation between Portalegre Shear Zone and the Carnaubais System Faults, contribute to the hypothesis of propagation of the Equatorial Margin efforts into the continent.